2020
DOI: 10.1371/journal.pone.0232611
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the pre-pitch entry practices of professional soccer substitutes may contribute towards improved movement-related performance indicators on match-day: A case study

Abstract: Modifying a soccer substitute's pre-pitch-entry activities may represent an opportunity to maximise physical performance and minimise injury-risk following match-introduction. Using a professional team that has previously participated in substitute profiling research, this follow-up case study investigated the effects of a modified match-day protocol that included substitutes; 1) performing a new pre-match warm-up alongside members of the starting team (as opposed to a separate substitute-only warm-up), 2) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 35 publications
2
26
2
Order By: Relevance
“…Whereas absolute HSR in the current study equated to <50% of whole-match values for players occupying outfield players (9, 14, 31), relative HSR of ~28.1 m•min -1 far exceeds the ~4.8-10.1 m•min -1 typically recorded across a playing bout for both partial-and whole-match players (7,9,19). Indeed, such values broadly reflect the relative HSR responses reported during the 'peak' 2-3 min period of match-play (13,17,20).…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…Whereas absolute HSR in the current study equated to <50% of whole-match values for players occupying outfield players (9, 14, 31), relative HSR of ~28.1 m•min -1 far exceeds the ~4.8-10.1 m•min -1 typically recorded across a playing bout for both partial-and whole-match players (7,9,19). Indeed, such values broadly reflect the relative HSR responses reported during the 'peak' 2-3 min period of match-play (13,17,20).…”
Section: Discussioncontrasting
confidence: 66%
“…Given the role of top-ups as a means of offsetting discrepancies in match-play demands, it is unsurprising that unused members of the match-day squad recorded generally greater absolute top-up responses compared with players who had experienced partial match-play (i.e., those substitutes who were deployed during the immediately preceding match). However, acknowledging that any match-exposure must also be considered when assessing an individual's overall match-day loading, and that considerable variation may exist in relation to a substitute's match demands, an existing study of English Championship soccer players indicated that substitutes typically covered just ~0.1 km of HSR following entry onto the pitch (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations